P PENINGKATAN KINERJA KEUANGAN LPD DESA ADAT PENGLATAN MELALUI PENGELOLAAN RISIKO KEUANGAN DI MASA PANDEMI COVID-19 - Ni Made Wulan Sari Sanjaya; Kadek Purnama Dewi (Politeknik Bisnis Indonesia, 2023)
During the Covid-19 pandemic, many LPDs were found to have experienced a decline in assets, even unable to obtain optimal profits. This condition makes the LPD's ability to increase assets lower. Thus, in order to produce optimal assets, management needs to carry out proper risk management. So this research is aimed at analyzing the financial performance of LPD Penglatan Traditional Village through risk management during the Covid-19 pandemic. This type of associative research with a quantitative approach. The data was obtained through the financial reports of the Penglatan Traditional Village LPD. The data analysis technique used is multiple linear regression analysis with the variables tested consisting of two X variables, namely Loan to Deposit Ratio (LDR/X1) and BOPO (X2). Meanwhile, ROA is a Y variable. The results show that there is an significantand positive effect between LDR on ROA. Meanwhile, a significant and negative effect was found between BOPO and ROA..